The Hippo signaling pathway: from multiple signals to the hallmarks of cancers - Zhu Ning; Yang Ruizeng; Wang Xiaodong; Yuan Liang; Li Xiaoyu; Wei Fang; Zhang Lei (Acta Biochimica et Biophysica Sinica, 2023)
Evolutionarily conserved, the Hippo signaling pathway is critical in regulating organ size and tissue homeostasis. The activity of this pathway is tightly regulated under normal circumstances, since its physical function is precisely maintained to control the rate of cell proliferation. Failure of maintenance leads to a variety of tumors. Our understanding of the mechanism of Hippo dysregulation and tumorigenesis is becoming increasingly precise, relying on the emergence of upstream inhibitor or activator and the connection linking Hippo target genes, mutations, and related signaling pathways with phenotypes. In this review, we summarize recent reports on the signaling network of the Hippo pathway in tumorigenesis and progression by exploring its critical mechanisms in cancer biology and potential targeting in cancer therapy.